Utilization of Antenatal Care Services in Dalit Communities in Gorkha, Nepal: A Cross-Sectional Study. (1st November 2018) - Awasthi, Mamata Sherpa; Awasthi, Kiran Raj; Thapa, Harish Singh; Saud, Bhuvan; Pradhan, Sarita; Khatry, Roshani Agrawal
Abstract : Background and Objective . Antenatal care (ANC) is one of the main components of maternal health. Utilization of safe motherhood is deprived in women who belong to low-caste groups like Dalit of Nepal. Low socioeconomic status, poor knowledge and awareness on obstetric complications, lack of decision-making autonomy, and limited health care options lead to underutilization of existing maternal health care service. The aim of this study was to ascertain the utilization of antenatal care services in terms of ANC visits with health personnel, receiving recommended period of iron tablets, consumption of antihelminthes and number of Tetanus Toxoid (TT) vaccines taken among child bearing women in Dalit community. Materials and Methods . Descriptive cross-sectional research design was used to conduct the study of 150 child bearing women of reproductive age (15-49 years) having at least one child up to three years of age in a Dalit community of Gorkha from March 2015 to March 2016. The data was collected from each mother by conducting face to face interview with each household by using a questionnaire. Result . The study revealed that mean age at marriage of respondents was 17.7 years and mean age at first pregnancy was 18 years. 44.6% of respondents experienced complication during last pregnancy, labour, and postpartum period in their last pregnancy. 59.3% of respondents stated that neighbors, relatives, and traditional healers were the best first contact person during health problem of women. 76.0% of respondents had attended antepartum visit during their last pregnancy whereas 24.0% of respondents did not attend any antepartum clinic. 68.3% of the mothers had consumed Iron/Folates within 45 days after delivery. Only 30.0% of respondents received antihelminthes (albendazole) while 70.0% of respondents had received TT Vaccines during their last pregnancy. Age, type of family, and education of the mothers were significantly associated with utilization of antenatal care services. Conclusion . Even though there is reasonable good utilization rate of antenatal service, the study revealed that low education and awareness among mothers, low socioeconomic condition, early marriage and pregnancy, inappropriate antenatal health check-up, and cultural taboos were significant factors affecting the satisfactory utilization of services among the Dalit community. Hence, there is a need to emphasize on raising awareness of Dalit mothers for receiving available prenatal services.